(3cJGH aj CfhGY GdJhMjOs ((3eMeO Hf YHO GdQDa s)
(3ChdgG (B:s
(3aJbhd GdJhMjO fhYGf JhMjO GdQHhHjI hgh Cf Gddg SHMGfg eJaQO HGdNdb hGdJOHjQ s
(3BNQgG (B:s
(3HMH YdjfG EJHGYge Udi Gddg Ydi SjOfG eMeO hBdg hSde hCUMGHg hSde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeS YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdJhMjO hGdedd hGdfMds